Maternal and neonatal outcome of twin pregnancy at a tertiary care center - Chaudhary, Vaishali; Thiyagarajan, Kamalpriya; Patil, Yogini; Gawali, Vijaykumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Twin pregnancies occurs in 2 to 4% of the total number of births. Also the perinatal mortality and morbidity associated with it is five to six times higher in comparison with singleton pregnancy. In developing countries, 287,000 annual maternal deaths and 3 million neonatal deaths contributes to 99% of such mortality as per records of the World Health Organization (WHO) estimates that 99% of the world’s annual occur in developing countries. Methods: This observational study included 50 women with twin pregnancy with gestational age of 26 weeks or more. Maternal and neonatal characteristics in twin deliveries at a tertiary care center were analyzed. High risk factors and it’s association with maternal and perinatal outcomes was analyzed. Results: Pregnancy induced hypertension (32%) was the commonest, Preterm rupture of membranes (PROM, 22%) was in the next order. Invitro fertilization (44%), malpresentation (26%) main indicators for lower segment cesarean section. Mean weight of first twin was 1.9±0.43 kg and for second twin it was 1.89±0.47kg (Table 1). Most of twins were diamniotic dichorionic (78%). Conclusions: Twin pregnancies are hazardous to both for the mother and the neonate. It is certainly high risk factor which needs early identifications of complications and timely management. Perinatal outcome largely depends on gestational age, birth weight, presentation, mode of delivery.